AGR2 predicts tamoxifen resistance in postmenopausal breast cancer patients - Hrstka, Roman; Brychtova, Veronika; Fabian, Pavel; Vojtesek, Borivoj; Svoboda, Marek (Disease markers, 2013)
Endocrine resistance is a significant problem in breast cancer treatment. Thus identification and validation of novel resistance determinants is important to improve treatment efficacy and patient outcome. In our work, AGR2 expression was determined by qRT-PCR in Tru-Cut needle biopsies from tamoxifen-treated postmenopausal breast cancer patients. Our results showed inversed association of AGR2 mRNA levels with primary treatment response (P = 0.0011) and progression-free survival (P = 0.0366) in 61 ER-positive breast carcinomas. As shown by our experimental and clinical evaluations, elevated AGR2 expression predicts decreased efficacy of tamoxifen treatment. From this perspective, AGR2 is a potential predictive biomarker enabling selection of an optimal algorithm for adjuvant hormonal therapy in postmenopausal ER-positive breast cancer patients.
Keywords: senioři; Oncogene Proteins; messenger RNA; Breast Neoplasms; tamoxifen; postmenopauza; senioři nad 80 let; mukoproteiny; proteiny; regulace genové exprese u nádorů; výsledek terapie; Middle Aged; onkogenní proteiny; studie případů a kontrol; Biomarkers, Tumor; Carcinoma; chemorezistence; Aged, 80 and over; ženské pohlaví; nádorové biomarkery; Postmenopause; RNA, Messenger; Humans; Drug Resistance, Neoplasm; Gene Expression Regulation, Neoplastic; lidé středního věku; Tamoxifen; Antineoplastic Agents, Hormonal; nádory prsu; Case-Control Studies; Mucoproteins; Female; Aged; Treatment Outcome; Proteins; lidé; hormonální protinádorové látky; karcinom